2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259861
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nuclear Delivery and Nuclear Body Localization of Antisense Oligo-Nucleotides using Degradable Polymersomes

Abstract: Delivery of antisense oligonucleotides, AON, presents many of the same challenges as delivery of any nucleic acid: charge, stability, cell uptake, endolysosomal escape, and entry into the nucleus. Here we demonstrate efficient delivery of AON after loading into biodegradable polymer vesicles or 'polymersomes'. We focus on AON delivery to muscle cells in vitro and in vivo because of the emergence of AON in therapeutic strategies directed at muscular dystrophies. To first clarify uptake kinetics without the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Being fully synthetic, the physiological properties of polymersomes can be easily manipulated to incorporate desirable characteristics that can have a dramatic effect on drug delivery (25, 45, 51). Polymersome‐delivered therapy has already been successfully tested in vivo (3032); hence, it is perfectly feasible that in vitro studies such as that described herein can be replicated in vivo and rapidly translated into the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being fully synthetic, the physiological properties of polymersomes can be easily manipulated to incorporate desirable characteristics that can have a dramatic effect on drug delivery (25, 45, 51). Polymersome‐delivered therapy has already been successfully tested in vivo (3032); hence, it is perfectly feasible that in vitro studies such as that described herein can be replicated in vivo and rapidly translated into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…To date, polymersomes have been used to administer anticancer therapy in vitro (paclitaxel and doxorubicin) and to shrink tumors in vivo (29, 30). They have also been used for the intracellular delivery of siRNA and antisense oligonucleotides (31, 32) or functional antibodies (28) and as transfection tools to deliver plasmid DNA into cells (33, 34). In the current study we show, for the first time, that polmersomes can deliver antibiotics to oral keratinocytes and that, once delivered, these can kill intracellular‐dwelling bacteria.…”
mentioning
confidence: 99%
“…A study demonstrated the specificity of an actively targeted polymeric vesicle via encapsulation and targeted release of a hydrophobic dye [77]. In addition, gene delivery has been demonstrated in vitro and in vivo , while simultaneously allowing molecular imaging of the polymersome [74,78,79]. Gd-DTPA and iron-oxide loaded PLGA nanoparticles have been used with US and MRI [80,81].…”
Section: Nanoparticlesmentioning
confidence: 99%